2007
DOI: 10.1002/per.642
|View full text |Cite
|
Sign up to set email alerts
|

Differences in personality characteristics between body‐modified and non‐modified individuals: associations with individual personality traits and their possible evolutionary implications

Abstract: After a long history of negative stigmatisation, the practices of tattooing and body piercing have become fashionable in the last decade. Today, 10% of the population in modern western societies have some form of body modification. The aim of this study was to quantify the demographic and personality traits of tattooed and pierced individuals and to compare them with a control group of individuals without body modifications. These comparisons are based on questionnaires completed by 359 individuals that invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 53 publications
(48 reference statements)
6
35
0
8
Order By: Relevance
“…In general, these prevalence rates are consistent with previous work showing that body piercings and tattoos are fairly common among the general population in Western countries, particularly among younger age groups (e.g., Forbes, 2001;Makkai & McAllister, 2001;Brooks, et al, 2003;Mayers, et al, 2003;Armstrong, et al, 2004;Laumann & Derick, 2006). Indeed, the prevalence rates of piercings and tattoos in the present study were very similar to those reported in neighboring Austria (see Wohlrab, et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, these prevalence rates are consistent with previous work showing that body piercings and tattoos are fairly common among the general population in Western countries, particularly among younger age groups (e.g., Forbes, 2001;Makkai & McAllister, 2001;Brooks, et al, 2003;Mayers, et al, 2003;Armstrong, et al, 2004;Laumann & Derick, 2006). Indeed, the prevalence rates of piercings and tattoos in the present study were very similar to those reported in neighboring Austria (see Wohlrab, et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…In terms of body piercings, prevalence reports have ranged between 4 and 56% (Carroll, et al, 2002;Brooks, Woods, Knight, & Shrier, 2003;Mayers, Moriarty, Judelson, & Rundell, 2003;Armstrong, Roberts, Owen, & Koch, 2004;Laumann & Derick, 2006;Skegg, Nada-Raja, Paul, & Skegg, 2007;Wohlrab, Stahl, Rammsayer, & Kappeler, 2007). Among a representative sample of British adults, for example, one survey estimated that 10% of all respondents had piercings at sites other than the earlobe (Bone, Ncube, Nichols, & Noah, 2008).…”
mentioning
confidence: 97%
“…In other words, when tattoos were more common in men, tattoos in women were unusual and so drew more attention from the respondent. Moreover, the locations for the tattoos are commonly used for real tattoos in men as well as women (Wohlrab, et al, 2007). Moreover, the locations for the tattoos are commonly used for real tattoos in men as well as women (Wohlrab, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Modified individuals were assessed as being higher on measures of autonomy, with women also being higher in impulsivity (Manuel and Sheehan 2007). Associations between the Big 5 personality factors and body modifications found that tattooed individuals had lower scores on Agreeableness and higher scores on Openness to Experience (Nathanson, Paulhus, and Williams 2006) while another study found the same correlation with Agreeableness but no difference on Openness to Experience (Wohlrab et al 2007).…”
Section: Personality Differencesmentioning
confidence: 93%